Water injection system for power augmentation and emission control for hydrogen-fuelled compression ignition engine / Adnan Roseli - Adnan, Roseli (2012)
The increase in demand and depletion of fossil fuels has led the search for alternative fuels become mandatory. Hydrogen is one of the promising alternative fuels for combustion engines and it can be used in compression ignition engine with the help from pilot ignition of diesel. Hydrogen-fuelled dual fuel compression ignition engine produces a reasonable increase in power output and thermal efficiency but suffers from higher concentrations ofHC, CO and NOx. In this research, experimental investigations have been conducted on performance and emission characteristics of a compression ignition engine running on hydrogen gaseous fuel. The experimental works have been carried out on a single cylinder, 4-stroke direct injection YANMAR LlOOAE compression ignition engine. Timed port injection for hydrogen and timed manifold water injection systems were developed in order to control its injection timing and duration. Electronic control unit (ECU) was used to fix injection timing of hydrogen fuel from 0°CA to 20°CA at constant flow rate of 3 LPH. Injection timings of water were in the range of 20°BTDC to 20° ATDC with variable injection duration of 20°CA and40°CA. Experimental results pertaining to performance and emission characteristics of HFCI engine with variable water injection timings are presented in detail. It is then compared with diesel alone and diesel-hydrogen operations. Numerical simulations based on the developed mathematical models are performed to study the emissions of diesel combustion with hydrogen and water addition. Numerical results are analyzed in order to validate experimental emissions characteristics of HFCI engine with and without water injection. In this study, the results indicate that water injection timing of 20° ATDC and duration of 20°CA has shown better engine performance due to increased gross indicated work, indicated thermal efficiency and it also has shown lower indicated specific energy consumption especially at 2000 RPM. Water injection timing of 20°BTDC and duration of 40°CA has shown the highest heat release rate and the longest ignition delay. In emission analysis, water injection timing of 0°CA and duration of 40°CA indicated the lowest C02 concentration throughout entire speed range. Water injection timing of 20°BTDC and duration of 20°CA has shown the lowest S02 emission. Water injection timing of 0°CA and duration of 20°CA has shown the lowest CO emission for higher speed range. Water injection timing of 20° ATDC and duration of 20°CA indicated the lowest HC emission and EGT throughout all engine speeds. All water injection timings indicated lower NOx concentration for entire speed range. Experimental emission characteristics have been validated and it is in good agreement with numerical simulation. It is concluded that water injection timing of 20° ATDC and duration of 20°CA is the optimum timing for power augmentation and better control of emissions. Generally, water injection system with optimum injection timing appears to be a promising method to enhance the performance and emissions quality of HFCI engine effectively.